1986
DOI: 10.1093/jac/17.6.811
|View full text |Cite
|
Sign up to set email alerts
|

Influence of ofloxacin, norfloxacin, nalidixic acid, pyromidic acid and pipemidic acid on human γ-interferon production and blastogenesis

Abstract: Several new quinolone derivatives were investigated for their influence on human lymphocyte blastogenesis and gamma-interferon production following concanavalin A stimulation. All the antimicrobials induced inhibition of lymphocyte DNA synthesis. The gamma-interferon measurements showed that nalidixic acid and norfloxacin have a negative influence on lymphokine production and release.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
11
1

Year Published

1986
1986
2009
2009

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 25 publications
(13 citation statements)
references
References 0 publications
1
11
1
Order By: Relevance
“…Cipro was unable to restore IFN-g production, but significantly upregulated LPS-stimulated splenocyte production of TNF-a, IL-1b and IL-6 compared with either non-Cipro-treated rats or controls. This is consistent with earlier findings with various quinolones at therapeutic levels (De Simone et al, 1986;Gollapudi et al, 1986;Bailly et al, 1991;Riesbeck and Forsgren, 1994;Katsuno et al, 2006). Cipro showed a consistent upregulation of IL-6 production of splenocytes in response to B-or T-cell mitogens, and this may be of benefit in chemotherapy-related sepsis as low Il-6 production from systemic immune compartments correlates with sepsis mortality (Adamik et al, 1997).…”
Section: Effects Of Cipro On Alterations Of Immune Competence After Csupporting
confidence: 90%
“…Cipro was unable to restore IFN-g production, but significantly upregulated LPS-stimulated splenocyte production of TNF-a, IL-1b and IL-6 compared with either non-Cipro-treated rats or controls. This is consistent with earlier findings with various quinolones at therapeutic levels (De Simone et al, 1986;Gollapudi et al, 1986;Bailly et al, 1991;Riesbeck and Forsgren, 1994;Katsuno et al, 2006). Cipro showed a consistent upregulation of IL-6 production of splenocytes in response to B-or T-cell mitogens, and this may be of benefit in chemotherapy-related sepsis as low Il-6 production from systemic immune compartments correlates with sepsis mortality (Adamik et al, 1997).…”
Section: Effects Of Cipro On Alterations Of Immune Competence After Csupporting
confidence: 90%
“…In studies in which the effects of quinolones on leukocyte function were measured, increased macrophage phagocytic capacity has been demonstrated by pefloxacin (3). In contrast, lymphocyte studies with quinolones have shown reduced mitogen-induced cell proliferation (difloxacin) and decreased DNA synthesis with norfloxacin and difloxacin (2,13). The effect of each quinolones on leukocyte function could not be clearly defined in our model.…”
Section: Discussioncontrasting
confidence: 61%
“…Forsgren and his group (8, 9, 10) have repeatedly reported an increase in JH-thymidine uptake by PHA and Con-A stimulated lymphocytes exposed to clinically relevant concentrations of ciprofloxacin and other quinolones. In contrast, other researches have found no change in uptake in ciprofloxacin exposed Iymphocytes or inhibition of uptake in cells exposed to ofloxacin, norfloxacin, pefloxacin and difloxacin (11,12,13). One possible explanation for these discordant results is the difference in incubation periods.…”
Section: Effect Of Quinolones On Human Lymphocytes Inmentioning
confidence: 78%